The Use of Zoom and WhatsApp Applications as a Communication Bridge for the Indo-Red Army Bekasi Community in Forming Cohesiveness during the Covid-19 Pandemic - Syari Harahap, Hamida; Adam Adami, Andi; Yasya, Wichitra (KnE Social Sciences, 2023)
This study aims to determine the use of Zoom and WhatsApp applications as a communication bridge in the Indo-Red Army Bekasi community in forming cohesiveness during the pandemic. The method used in this study is a descriptive qualitative method, with interview, observation, documentation and content analysis techniques for mass media. This research uses the concept of group cohesiveness to see how the cohesiveness exists within the Indo-Red Army Bekasi community during of the Covid-19 pandemic. The results of this research are that the chairman of the Indo-Red Army Bekasi community seeks to maintain communication and cohesiveness during the Covid-19 pandemic by using the Zoom and WhatsApp applications. The Zoom application is used for watching the Manchester United club game together online and having discussions after the game, while the WhatsApp application is used as a forum for communicating with all members and online meetings. By using these two applications as a communication bridge, they have formed solidarity and cohesiveness in the Indo-Red Army Bekasi community. Keywords: football fan community, group cohesiveness, virtual communication media